Development of Science and Technology in the Perspective of Q.S. Ar-Rahman verse 33 and its benefits for Islamic society - Abdul Baasith Zulfikar; Didik Himmawan; Lauria Khaila Ahrom (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
This article discusses Islamic views on technology in this day and age, progress cannot be stopped. The world is becoming more advanced and more modern. With this progress, science and technology are increasingly advanced and developing, even becoming more modern. In Islam, science and technology are a necessity and must be in accordance with Islamic views. Science and technology without an Islamic view, there will be chaos both physically and non-physically. The methodology in the paper uses a descriptive qualitative approach, this research is realized by interpreting the main topic variables and then connecting them with other data variables, with the results presented in sentences. The research conclusion, which can be understood, is that there are at least two main roles of Islam in the development of science and technology; First, making Islamic Aqidah a paradigm of thought and science. Second, making Islamic sharia the standard for the use of science and technology.